GOTONG ROYONG DALAM UPACARA PERKAWINAN PADA MASYARAKAT DI JORONG KUBU ANAU KENAGARIAN MANGGOPOH LUBUK BASUNG AGAM - Khairi, Ima Latul; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This researce was carried out at Jorong Kubu Anau Kenagarian Manggopoh districts Lubuk Basung by taking the data in the office Kenagarian Manggopoh. The purpose of researce to know implementation of mutual cooperation in raditions of marriage until baretong. The topic of this research is the result of baretong the implementation of the marriage. The study used qualitative research methods. This study consisted of six informants, of them as key informants and two as informants selected by using purposive sampling technique. The data instruments are observations, in-depth interviews, and documentation. From the researce done , the authers faound that intradition mutual cooperation in the implementation of marriage in the Jorong Kubu Anau is as follows: custom marriage and the marriage process stage starts from, rapat pusako, maantaan asok, tibang tando, duduk mamak, mengundang, batagak pondok, baralek, and the last is baretong. The custom of baretong as tradition of mutual cooperation among others is the implementation af baretong, arrangement of baretong implementation activities, tools or facilities used when baretong, baretong participants and their functions and when the show is baretong and when in society. The difference between mens and womens, the result of tradition of profit or loss, factors affecting baretong results, as well as the types of donation given when baretong. The purpose of mutual cooperation in marriage is to alleviate the costs borne. Each stage of the tradition of marriage contains elements of mutual cooperation. Keywords : marriage ceremony, mutual cooperation, baretong